Echocardiographic assessment of left ventricular radial strain to differentiate cardiac amyloidosis from Fabry disease. (3rd October 2022) - Steudel, T; Mattig, I; Romero Dorta, E; Barzen, G; Frumkin, D; Laule, N; Al Daas, M; Spethmann, S; Knebel, F; Canaan-Kuhl, S; Stangl, K; Hahn, K; et al.
Abstract: Background: Left ventricular (LV) wall thickening is a typical echocardiographic finding in infiltrative cardiomyopathies like cardiac amyloidosis (CA) and Fabry disease (FD). The discrimination of both infiltrative diseases remains challenging by standard as well as 2D speckle tracking echocardiography (2DSTE)-based analysis of longitudinal LV strain patterns. Over the recent years, a constant development in image quality and data processing provided better possibilities to analyse layer specific myocardial deformation indices. With regards to FD, specific layer LV strain patterns may be useful to rule-in FD in patients with suspected infiltrative cardiomyopathy. Purpose: The aim of the present study was to investigate differences and the diagnostic value of layer specific 2D STE-based radial LV strain indices in CA and FD. Methods: Next to standard parameters of a comprehensive echocardiographic assessment (Vivid E9 or E95, GE Vingmed, Horton, Norway, with an M5S 1.5–4.5MHz transducer), we retrospectively analysed the transmural radial LV strain (GSradial), the subendocardial radial LV strain (GSendo), the subepicardial radial LV strain (GSepi), and the strain gradient (GSendo − GSepi) (EchoPAC software, GE) in FD patients and CA patient from the amyloidosis registry at our study site. A Receiver operating curve (ROC) analysis was used to assess the diagnostic value of the respective LV strain values and the layer-specific strain gradient to discriminate FD and CA. Results: A total of 38 FD and 40 CA patients were included in our analyses. In patients with FD, GSepi showed a marked impairment. LV radial and layer strain were significantly reduced in CA compared to FD patients [GSradial −12.0 (−16.2 to −9.9) in CA vs. −17.7 (−20.5 to −14.6) in FD; p<0.001); GSendo (−20.6 (−27.0 to −15.7) in CA vs. −30.0 (−32.0 to −25.6) in FD; p<0.001); and GSepi (−7.4 (−8.9 to −4.8) in CA vs. −9.1 (−11.86 to −7.6) in FD; p<0.001)]. The gradient of GSendo and GSepi was significantly lower in patients with CA compared to FD (−14.0±5.6 in CA vs. −19.4±4.3 in FD respectively; p<0.001). GSendo held the highest diagnostic accuracy to discriminate CA and FD (area under the curve [AUC] 0.83, 95% confidence interval [CI] 0.73–0.92). The layer-specific strain gradient GSendo − Gsepi showed an AUC of 0.79 (CI 0.69 to 0.89). Conclusion: Layer-specific strain analysis demonstrated significantly reduced strain values in CA patients compared to FD. The analysis of GSendo held a high diagnostic accuracy to discriminate FD and CA in patients. The integration of layer-specific LV strain indices into the diagnostic work-up may improve the management of patients with an unclear thick heart pathology in future. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Alnylam Pharmaceuticals (Cambridge, MA, USA)